The Right To Be Forgotten According To Žižek's Paradox - Antonius Maria Laot Kian (Mimbar Hukum, 2025)
Abstract This article analyzes the paradox of implementing the right to be forgotten in Indonesia through the Lacanian psychoanalytic perspective developed by Slavoj Žižek. This study highlights the structural impossibility of completely erasing digital trace despite the existence of legal mechanisms that protect individual privacy, an issue that is increasingly relevant in the digital age. Previous studies have emphasized procedural or technical aspects, whereas this research examines the psychoanalytic and philosophical dimensions of digital forgetting. An analysis of Article 26 of the ITE Law shows that the court procedures in question produce new legal documentation, reinforcing rather than erasing digital traces. Žižek's concepts of the Real, the Symbolic, and the Imaginary show how these traces remain, creating a cycle of repetition and return of the repressed that challenges conventional legal approaches. This study concludes that the right to be forgotten cannot be fully realized through technical or procedural mechanisms, but rather through fundamental aspects of modern subjectivity, digital identity, and the limitations of law in dealing with digital reality. Abstrak Artikel ini menganalisis paradoks implementasi hak untuk dilupakan di Indonesia melalui perspektif psikoanalisis Lacanian yang dikembangkan Slavoj Žižek. Penelitian ini menyoroti ketidakmungkinan struktural untuk sepenuhnya menghapus jejak digital meskipun ada mekanisme hukum yang melindungi privasi individu, yang menjadi masalah yang semakin relevan di era digital. Studi sebelumnya lebih menekankan aspek prosedural atau teknis, sedangkan penelitian ini menelaah dimensi psikoanalitis dan filosofis dari pelupaan digital. Analisis Pasal 26 UU ITE menunjukkan bahwa prosedur pengadilan yang dimaksud justru menghasilkan dokumentasi hukum baru, yang memperkuat alih-alih menghapus jejak digital. Konsep Žižek tentang Real, Simbolik, dan Imajiner menunjukkan bagaimana jejak tersebut tetap ada, menciptakan siklus repetisi dan return of the repressed yang menantang pendekatan hukum konvensional. Penelitian ini menyimpulkan bahwa hak untuk dilupakan tidak dapat diwujudkan sepenuhnya melalui mekanisme teknis atau prosedural, melainkan melalui aspek fundamental subjektivitas modern, identitas digital, dan keterbatasan hukum dalam menghadapi realitas digital.